Syzygium polyanthum(Wight) Walp.: (Botani, Metabolit Sekunder dan Pemanfaatan) - Marina Silalahi (Jurnal Dinamika Pendidikan, 2017)
ABSTRACT Syzygium polyanthum (Wight) Walp. or known as bay leaf is one of the species of the Myrtaceae have been used as a traditional medicine by various ethnicities, especially in Southeast Asia. The utilization of Syzygium polyanthum as a medicine is related to its secondary metabolite content. The article aims to know the relationship of secondary metabolites and the utilization of Syzygium polyanthum as a traditional medicine as well as scientific evidence. This paper is based on literature review both online and offline in the form of books and scientific journals. Syzygium polianthum contains a variety of secondary metabolites, especially essential oils, tannins, flavonoids, and terpenoids. As a traditional medicine ingredient, Syzygium polyanthum is used as a drug of diabetes mellitus, stomach disorder, overcoming haemorrhoids disease, diarrhea, skin diseases, freshener, hypertension and cholesterol. Scientifically Syzygium polyanthum has bioactivity as an antimicrobial, antioxidant, antidiabetic, and anti cholesterol. Keywords: Syzygium polyanthum, essential oil, antioxidant ABSTRAK Syzygium polyanthum(Wight) Walp. atau yang dikenal dengan nama daun salam merupakan salah satu spesies dari famili Myrtaceae yang digunakan sebagai obat tradisional oleh berbagai etnis khususnya di Asia Tenggara.Pemanfaatan Syzygium polyanthum sebagai obat berhubungan dengan kandungan metabolit sekundernya. Artikel bertujuan untuk menkaji hubungan metabolit sekunder dan pemanfaatan Syzygium polyanthumsebagai obat tradisional serta bukti ilmiahnya. Tulisan ini didasarkan pada kajian literatur baik secara online dan offline berupa buku dan jurnal ilmiah. Syzygium polianthum mengandung berbagai metabolit sekunder terutama essential oils, tannin, flavonoid, dan terpenoid. Sebagai bahan obat tradisional, Syzygium polyanthum digunakan sebagai obat diabetes mellitus, gangguan lambung, mengatasi penyakit haemorrhoids, diarrhea, penyakit kulit, penyegar, hipertensi dan kolesterol. Secara ilmiah telah Syzygium polyanthum memiliki bioaktivitas sebagai antimikroba, antioksidan, antidiabetes, dan anti kolesterol. Kata kunci:Syzygium polyanthum, essensial oil, antioksidan